Hubungan Tingkat Pengetahuan dengan Kecemasan Pre Anestesi Spinal Pada Pasien Sectio Caesarea di Rumah Sakit TK III Salak Bogor - Suryana, Ucup; Susanti, Indri Heri; Khasanah, Suci (Viva Medika, 2023)
Background: Surgery and anesthesia are actions that bring stress, because there is a threat to the integrity of one's body and soul. The existence of this stress can cause an anxiety condition. Patients who will undergo surgery will experience preoperative and pre-anesthesia anxiety in various levels. Purpose: The purpose of the study was to determine the relationship between knowledge level and pre spinal anesthesia anxiety in sectio caesarea surgery at TK III Salak Hospital, Bogor. Methods: The research design used was descriptive correlational with a cross sectional approach. The population in this study were patients who were about to give birth by sectio caesarea at the TK III Salak Hospital, Bogor. The sampling technique used was purposive sampling using the Slovin formula so that 53 respondents were obtained according to the inclusion and exclusion criteria. The analysis used is spearman rank correlation. Results: Most of the respondents had sufficient knowledge of 28 people (52.8%) and 23 people (43.4%). The results of the statistical test showed a significant relationship (p value = 0.006) between knowledge and pre-spinal anesthesia anxiety with the Spearman correlation value of 0.370. Conclusion: There is a relationship between knowledge and pre-spinal anesthesia anxiety in sectio caesarea patients at TK III Salak Hospital, Bogor